2016
DOI: 10.4238/gmr.15027616
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of the polarity of macrophages regulated by IL-37 on atherosclerosis

Abstract: ABSTRACT.As an anti-inflammatory cytokine, interleukin-37 (IL-37) provides certain protective effects against inflammatory and autoimmune diseases. Recent reports indicate that IL-37 is expressed in foam cells of atherosclerotic plaques in both the coronary and carotid arteries of humans, suggesting the possible involvement of IL-37 in the pathogenesis and progression of atherosclerosis. Current evidence supports the protective role that IL-37 plays against atherosclerosis via the regulation of different subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Because macrophages are central to disease pathogenesis in various ways from the early to late stages of atherosclerosis, they provide a valuable delivery system for expression of anti-inflammatory mediators, such as IL-37, to alter the plaque microenvironment (19). The anti-inflammatory benefits of IL-37 have been widely accepted, and its potential as a therapeutic measure for reducing the pathogenesis of atherosclerosis has been discussed (20), yet exploration of its effects on plaque development has been limited to systemic treatment with rIL-37 (21,22). The delivery of IL-37 directly to the plaque microenvironment via macrophage-specific expression has not been investigated.…”
mentioning
confidence: 99%
“…Because macrophages are central to disease pathogenesis in various ways from the early to late stages of atherosclerosis, they provide a valuable delivery system for expression of anti-inflammatory mediators, such as IL-37, to alter the plaque microenvironment (19). The anti-inflammatory benefits of IL-37 have been widely accepted, and its potential as a therapeutic measure for reducing the pathogenesis of atherosclerosis has been discussed (20), yet exploration of its effects on plaque development has been limited to systemic treatment with rIL-37 (21,22). The delivery of IL-37 directly to the plaque microenvironment via macrophage-specific expression has not been investigated.…”
mentioning
confidence: 99%
“…IL-37 is involved in the suppression of innate and adaptive immunity (Boraschi et al 2011;Chen and Fujita 2015;Ye et al 2014). Recent reports indicate that IL-37 plays important roles in inflammatory disease (Charrad et al 2016;Ye et al 2014;Zhao et al 2014b), infectious disease (Anuradha et al 2016;Hojen et al 2015;Samarani et al 2016), cancer (Ding et al 2016;Ge et al 2016) and angiocardiopathy (Huang et al 2016;Yu et al 2016). However, the exact mechanisms of IL-37 in human disease remain to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Boraschi et al found that IL‐37 was expressed in the foam‐like cells of atherosclerotic coronary and carotid artery plaques, suggesting that IL‐37 is associated with the activation of macrophages and the shift from macrophages to foam cells. Huang et al found IL‐37 effectively decreased the area ratio between the aorta plaque and vascular cavity. They also observed IL‐37 inhibited M1 macrophages induction from peripheral monocytes by ox‐LDL and facilitated the transformation of macrophages into M2 cells .…”
Section: The Role In Cardiovascular Diseasesmentioning
confidence: 99%
“…Huang et al found IL‐37 effectively decreased the area ratio between the aorta plaque and vascular cavity. They also observed IL‐37 inhibited M1 macrophages induction from peripheral monocytes by ox‐LDL and facilitated the transformation of macrophages into M2 cells . These results indicate that IL‐37 may prevent atherosclerosis by modulating macrophage polarity.…”
Section: The Role In Cardiovascular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation